Development of a competency framework for a specialist dementia service. Issue 1 (8th April 2014) - Smythe, Analisa; Jenkins, Catharine; Bentham, Pete; Oyebode, Jan
Abstract : Purpose: – The purpose of this paper is to discuss the development of a competency framework for staff working in a specialist service for people with dementia. Design/methodology/approach: – A qualitative and purposive methodology was used and included focus groups, questionnaires and interviews. Content analysis together with synthesis of literature was used to generate the competency framework. Findings: – A competency framework was developed with eight main clusters. These were: skills for working effectively with people with dementia and their families; advanced assessment skills; enhancing psychological well-being; understanding behaviours; enhancing physical well-being; clinical leadership; understanding ethical and legal issues; and demonstrating skills in personal and professional development. Research limitations/implications: – Further research is needed to include service user perspectives. Practical implications: – The framework could be implemented in practice by managers, health care professionals and training providers as a tool to identify strengths and limitations in knowledge skills and attitudes and to identify areas for competency development through specific training. Originality/value: – The competency framework contributes to the development of a training curriculum for staff working within a specialist service.